Quantum-Classical Correspondences for Locally Symmetric Spaces - Hilgert, Joachim (Symmetry in Geometry and Analysis, Volume 2)

Flight due to climate change in Jostein Gaarder’s novel 2084: Noras’s World - Jagdschian, Larissa Carolin (Filoteknos: Migration Narratives: Staying, Leaving, and Returning in Children's and Young Adult Literature)

Eine Kultur des Teilens hochschulübergreifend durch OER voranbringen - Weber, Tassja; Kober, Sabine; Lewa, Carmen; Scherer, Elisabeth; Schotemeier, Sarah (Digitales Lehren und Lernen an der Hochschule. Strategien - Bedingungen - Umsetzung)

Untersuchung der Eignung von Eisen-/Mangan-Oxiden aus einer Sprayflammensynthese für die SCR - Maier, Lukas; Beimdiek, Janis

The Sacred Veil. Zum 60. Geburtstag von Charles Anthony Silvestri, zum 20. Todestag von Julia Lawrence Silvestri, zum 55. Geburtstag von Eric Whitacre - Schroeter-Wittke, Harald (Praktische Theologie)

Information Circularity Assistance based on extreme data - Gräßler, Iris; Weyrich, Michael; Pottebaum, Jens; Kamm, Simon (at - Automatisierungstechnik)
This paper presents the concept of Information Circularity Assistance, which provides decision support in the early stages of product creation for Circular Economy. Engineers in strategic product planning need to proactively predict the quantity, quality, and timing of secondary materials and returned components. For example, products with high recycled content will only be economically sustainable if the material is actually available in the future product life. Our assumption is that Information Circularity Assistance enables decision makers to incorporate insights from extreme data – high-volume, high-velocity, heterogeneous and distributed data from the product life – into product creation through intelligent Digital Twins. Artificial Intelligence can help to derive sustainable actions in favor of circular products by processing extreme data and enriching it with expert knowledge. The research contributes in three key dimensions. First, a comprehensive literature review is conducted. This review covers concepts of intelligence in Scenario-Technique for strategic product planning, Digital Twin-based analysis of extreme data and relevant technologies from Data Science and Artificial Intelligence. In all areas, the state of the art and emerging trends are identified. Secondly, the study identifies information needs along the steps of the Scenario-Technique and information offerings based on Digital Twins. The concept of Information Circularity Assistance results from the coupling of these demands and offerings, extending the Scenario-Technique beyond traditional expert-based methods. Third, we extend existing Digital Twin methods used in circularity and discuss the deployment of Data Science and Artificial Intelligence algorithms within the product creation process. Our approach uses extreme data to provide a strategic advantage in optimizing product life cycle planning, which is illustrated by two sample applications. The aim is to provide Information Circularity Assistance that will support experienced product planners, developers, and decision makers in the future.
Keywords: Scenario-Technique; Artificial Intelligence; Digital Twin; Large Language Models

Hybrid Decision Support in Product Creation - Improving performance with data science and artificial intelligence - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Stark, Rainer; Thoben, Klaus-Dieter; Wiederkehr, Petra (Industry 4.0 Science)
Technical systems are characterized by increasing interdisciplinarity, complexity and networking. A product and its corresponding production systems require interdisciplinary multi-objective optimization. Sustainability and recyclability demands increase said complexity. The efficiency of previously established engineering methods is reaching its limits, which can only be overcome by systematic integration of extreme data. The aim of "hybrid decision support" is as follows: Data science and artificial intelligence should be used to supplement human capabilities in conjunction with existing heuristics, methods, modeling and simulation to increase the efficiency of product creation.
Keywords: AI; artificial intelligence; Data Science; decision support; extreme data; Künstliche Intelligenz; product creation; product development

Cortical changes associated with an anterior cruciate ligament injury may retrograde skilled kicking in football: preliminary EEG findings - Piskin, Daghan Yüksel; Cobani, Gjergji; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Scientific Reports)
Abstract Anterior cruciate ligament injuries (ACLi) impact football players substantially leading to performance declines and premature career endings. Emerging evidence suggests that ACLi should be viewed not merely as peripheral injuries but as complex conditions with neurophysiological aspects. The objective of the present study was to compare kicking performance and associated cortical activity between injured and healthy players. Ten reconstructed and 15 healthy players performed a kicking task. Kicking biomechanics were recorded using wearable inertial measurement unit sensors. Cortical activity was captured with a 64-electrode mobile electroencephalography. Multiscale entropy (MSE) analysis of biomechanics revealed increased variability in foot external rotation among injured players. Source-derived event-related spectral perturbations indicated significant differences in posterior alpha and frontal theta oscillations between the two groups. Furthermore, kick-related complexity of these regions as indexed by MSE was reduced in injured players at medium and coarse scales. Our findings suggest sensorimotor changes during kicking in injured players, which may necessitate compensatory strategies involving augmented attention at the cost of processing visuospatial information. This conflict may hinder the integration of task-relevant information across distributed networks. Our study provides preliminary insights into the neurophysiological implications of ACLi within football context and underscores the potential for prospective research.

Phänomenologie der Tafelkunst. Eine kulinarische Einladung zum Essen und Philosophieren mit Bernhard Waldenfels - Albus, Vanessa (Phänomenologie, Transformation und philosophische Bildung. Philipp Thomas zum 60. Geburtstag)

Sprachhandlungen und Sprachmittel in der Analytischen Geometrie am Beispiel des Skalarprodukts - Lomas, Olga; Wessel, Lena (Beiträge zum Mathematikunterricht 2024. 57. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Viscous fingering in adhesive bonding - Al Trjman, Mohamad; Salten, Alexander Heinrich Johannes; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Riese, Julia; Kenig, Eugeny (International Journal of Adhesion and Adhesives)

Influence of microstructures on liquid spreading on inclined plates: A CFD based study - Dechert, Christopher; Kenig, Eugeny Y. (Chemical Engineering Science)

Untersuchung zur Vergleichbarkeit von verschiedenen Methoden zur Bestimmung der effektiven Phasengrenzflächen - Dechert, Christopher; Riese, Julia; Franke, Patrick

Bewertung des Potentiales der Elektrobenetzung für Trennkolonnen - Dechert, Christopher; Riese, Julia

Die LIFT: Lernwerkstatt Inklusion und individuelle Förderung am Technologiepark der Universität Paderborn - Ellersiek, Annchristin; Kottmann, Brigitte; Möbius, Henning; Timmermanns, Franziska; Wapelhorst, Jule (Atlas der Hochschullernwerkstätten. Ein (un-)vollständiges Kompendium.)

Die Lernwerkstatt an der Universität Bielefeld: Ein gemeinsamer Ort, ein Ort für gemeinsames Lernen - Kottmann, Brigitte; Stets, Mona (Atlas der Hochschullernwerkstätten. Ein (Un-)vollständiges Kompendium.)

A novel welding schedule for expanding the expulsion-free process window in resistance spot welding of dissimilar joints with ultra-high strength steel - Yang, Keke; Wang, Zhuoqun; Haak, Viktor; Olfert, Viktoria; El-Sari, Bassel; Hein, David; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)

Philosophy’s 25-Years Principle: Philosophy between Intuitive Understanding and Discursive Reasoning - Milkov, Nikolay (Journal of Research in Philosophy and History)
The present paper has two objectives. First, it explicates the story, initially portrayed by Eckart Förster, that philosophy allegedly started with publishing of Kant’s CPR and ended a quarter century later when Hegel’s Phenomenology of Mind appeared. We address the questions in what sense this happened and how is this development to be interpreted? Secondly, we demonstrate that similar radical transition from new, “true” beginning of philosophy to its apparent finishing took place in two other, high profile occasions in the history of Western philosophy, in two key points of its development: in the years 390-365 bc, between the early and the late Plato, and between 1898 and 1922, between Russell and Wittgenstein’s Tractatus. These three short-lived, spectacular transitions from philosophy’s alleged start to its alleged ultimate accomplishment give us good reason to speak about a specific 25-years principle in philosophy. In a peculiar way, this principle reveals philosophy’s true nature.
Keywords: Aristotle; Hegel; Kant; Plato; Russell; Wittgenstein

Fractional Variational Integrators Based on Convolution Quadrature - Hariz Belgacem, Khaled; Jiménez, Fernando; Ober-Blöbaum, Sina (Journal of Nonlinear Science)
Abstract Fractional dissipation is a powerful tool to study nonlocal physical phenomena such as damping models. The design of geometric, in particular, variational integrators for the numerical simulation of such systems relies on a variational formulation of the model. In Jiménez and Ober-Blöbaum (J Nonlinear Sci 31:46, 2021), a new approach is proposed to deal with dissipative systems including fractionally damped systems in a variational way for both, the continuous and discrete setting. It is based on the doubling of variables and their fractional derivatives. The aim of this work is to derive higher-order fractional variational integrators by means of convolution quadrature (CQ) based on backward difference formulas. We then provide numerical methods that are of order 2 improving a previous result in Jiménez and Ober-Blöbaum (J Nonlinear Sci 31:46, 2021). The convergence properties of the fractional variational integrators and saturation effects due to the approximation of the fractional derivatives by CQ are studied numerically.

Received and Perceived Peer Acceptance in Relation to Enjoyment, Social Competence, and Physical Activity in Primary School Physical Education and the Role of Peer-Relatedness Need Satisfaction - de Bruijn, Anne G.M.; Grimminger-Seidensticker, Elke (Journal of Teaching in Physical Education)